PENGGUNAAN FADs (Fish Aggregating Devices) PADA ALAT TANGKAP TANGKUL DI DANAU TELUK KOTA JAMBI - tussadiah, Arifa; Lisna, Lisna; Ramdhani, Farhan; Nelwida, Nelwida; Gelis, Ester Restiana Endang; Ramadan, Fauzan (Mantis Journal of Fisheries, 2025)
In Teluk Lake, Jambi City, fishermen face productivity constraints when catching fish. Research on using Fish Aggregating Devices (FADs) is necessary to enhance effectiveness and efficiency. This study, conducted in March 2024 in Teluk Lake, Tanjung Pasir Village, Jambi City waters, examines the use of FADs with liftnet fishing gear. The main findings of the research show that using FADs significantly increases catch yields and reduces fishermen's operational costs. The research methodology involved experimental fishing with a t-test to compare the catch results of liftnet using FADs and without FADs. The research showed the capture of 8 types of fish from two repetitions with two treatments (liftnet with FADs and without FADs). The total catch was 150 fish weighing 9.313 g. Catches using FADs reached 114 fish (7.219 g), while those without FADs were only 36 (2.094 g). Lambak fish showed significant results, with 79 fish (3.910 g) caught using FADs compared to 18 fish (781 g) without FADs. The T-test analysis revealed a significant difference (P<0.01) in catch results between the two treatments, both in terms of quantity (T hit​>T tab​ (2.93 > 2.10) and weight (T hit​>T tab ​ (114.60 > 2.10)). This research has practical implications, as it demonstrates that using FADs can significantly increase the quantity and weight of catches, providing valuable insights for fishery methods.